2020
DOI: 10.1161/circulationaha.119.044805
|View full text |Cite
|
Sign up to set email alerts
|

Signalosome-Regulated Serum Response Factor Phosphorylation Determining Myocyte Growth in Width Versus Length as a Therapeutic Target for Heart Failure

Abstract: Background: Concentric and eccentric cardiac hypertrophy are associated with pressure and volume overload, respectively, in cardiovascular disease both conferring an increased risk of heart failure. These contrasting forms of hypertrophy are characterized by asymmetric growth of the cardiac myocyte in mainly width or length, respectively. The molecular mechanisms determining myocyte preferential growth in width versus length remain poorly understood. Identification of the mechanisms governing asymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 64 publications
1
38
0
Order By: Relevance
“…ERK activity is also controlled via several phosphatases to regulate the duration of the transduced signal. While the dephosphorylation of ERK may be achieved by Ser/Thr [ 12 ] or Tyr phosphatases [ 13 ], there also exist specialized dual specificity phosphatases (DUSPs) that function to dephosphorylate both residues concurrently. These DUSPs comprise a phosphatase domain with a conserved catalytic site with Asp, Cys, and Arg residues within a flexible enzymatic pocket to accommodate phosphorylated targets [ 14 ].…”
Section: The Erk1/2 Signaling Modulementioning
confidence: 99%
See 1 more Smart Citation
“…ERK activity is also controlled via several phosphatases to regulate the duration of the transduced signal. While the dephosphorylation of ERK may be achieved by Ser/Thr [ 12 ] or Tyr phosphatases [ 13 ], there also exist specialized dual specificity phosphatases (DUSPs) that function to dephosphorylate both residues concurrently. These DUSPs comprise a phosphatase domain with a conserved catalytic site with Asp, Cys, and Arg residues within a flexible enzymatic pocket to accommodate phosphorylated targets [ 14 ].…”
Section: The Erk1/2 Signaling Modulementioning
confidence: 99%
“…Genetic ablation of GATA4 precludes hypertrophy, and this phenotype was not found to be rescued in activated MEK1 transgenic mice, suggesting GATA4 as a critical mediator of the MEK1–ERK pathway in the heart [ 108 ]. Recently, ERK effector RSK3 was identified to phosphorylate another transcription regulator, serum-responsive factor (SRF), where downstream signaling modulates cardiomyocyte growth in width, which is essential to concentric hypertrophy [ 12 ]. Recent reports also indicate crosstalk between ERK and transcription factor STAT3 signaling to mediate cardioprotection in myocytes treated with doxorubicin, again highlighting the importance of the ERK pathway for the integration of stress responses in the heart [ 109 ].…”
Section: Integration Of Erk1/2 Signaling For Cardiomyocyte Homeostasis and Stress Responsesmentioning
confidence: 99%
“…A recent study by Li et al have shown that dynamic regulation of SRF serine 103 phosphorylation by RSK3 and PP2A significantly impacts phenylephrine-induced gene transcription in cardiomyocytes. Specifically, the authors demonstrate, using ChIP-seq and PRO-seq, that the phosphomimetic SRF S103D appears to promote the association of SRF with enhancers, facilitate the recruitment of the basal transcription machinery, and preferentially augment the expression of early response and hypertrophic genes ( Li J. et al, 2020 ). Similar strategies could exploited to determine how the SRF S234D mutant influence the endothelial transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…We next considered that FGF21 might drive concentric remodeling in the presence of other stress stimuli. The α-adrenergic agonist phenylephrine induces a selective growth in width of cultured ARVM, while the β-adrenergic agonist isoproterenol induces growth in both width and length, resulting in a more symmetric ARVM hypertrophy (Li et al, 2020a). Co-treatment with FGF21 did not significantly further increase the prominent growth in width induced by phenylephrine or isoproterenol (Figure 2E-H).…”
Section: Fgf21 Promotes the Concentric Hypertrophy Of Adult Rat Ventricular Myocytes In Vitromentioning
confidence: 92%
“…Concentric cardiac hypertrophy is characterized by an increase in relative wall thickness (left ventricular wall thickness to internal diameter ratio) that is primarily a reflection of increased cardiac myocyte width, while, in contrast, eccentric cardiac hypertrophy is characterized by decreased relative wall thickness and relative myocyte lengthening. Concentric hypertrophy can be induced by activation of an extracellular signal-regulated kinase 1/2 (ERK1/2) -p90 ribosomal S6 kinase type 3 (RSK3) -serum response factor (SRF)-dependent gene expression regulatory pathway (Kehat et al, 2011;Li et al, 2020a;Passariello et al, 2016). It has been observed that in cardiac myocytes FGF21 activates ERK1/2 and, like ERK1/2 gene deletion, unstressed FGF21 knock-out mice exhibit eccentric cardiac hypertrophy (Planavila et al, 2013).…”
Section: Introductionmentioning
confidence: 99%